Experiencias en teleformación de archivos en Castilla y León - Quesada, José Antonio Robles (Tábula, 2010)
La f The traditional classroom training currently lives with distance learning. The records management and archive administration training is no stranger to this trend. Castilla y León Administration has always included training courses for records management in their formative plans. This article describes the first experience of adapting these training to e-learning environment during 2009, and briefly identifies some of the criteria and resources used to carry it out. RECORDS MANAGEMENT AND ARCHIVE ADMINISTRATION TRAINING / DISTANCE LEARNING / E-LEARNING / MOODLE / PUBLIC ADMINISTRATION SCHOOL OF CASTILLA Y LEON / INFORMATION TECNOLOGY ormación tradicional presencial convive actualmente con la teleformación. La formación en materia de archivos no es ajena a esa tendencia. La Administración de Castilla y León ha incluido siempre en sus planes formativos cursos de archivos de oficina. En este artículo se describe la primera experiencia de adaptación de estas acciones formativas al ámbito online durante el año 2009, y se señalan someramente algunos de los criterios y recursos empleados para llevarlo a cabo. FORMACIÓN ARCHIVÍSTICA / TELEFORMACIÓN / E-LEARNING / MOODLE / ESCUELA DE ADMINISTRACIÓN PÚBLICA DE CASTILLA Y LEÓN (ECLAP) / TECNOLOGÍAS DE LA INFORMACIÓN